Teachers' opinions on the use of artificial intelligence in electronic environments and its obstacles- Case Study: The Syrian Educational Platform (Journal of Hama University, 2026)
This research aimed to identify teachers' opinions on the use of artificial intelligence in the teaching and evaluating via Syrian educational platform and its obstacles, and the impact of variables (training courses, academic qualification, and number of years of experience) on that. In order to achieve the research objectives, the descriptive analytical approach was used by designing a questionnaire consisting of (15) statements distributed over two axes, and an open question about the obstacles to the use of artificial intelligence in Syrian educational platforms. The research sample consisted of (126) male and female teachers participating in providing lessons via the Syrian educational platform from various Syrian governorates. The research concluded that the degree of teachers' opinions on the use of artificial intelligence in the teaching and evaluating via the Syrian educational platform is high, the research identified some of the obstacles that prevent teachers from using artificial intelligence in Syrian educational platforms from the point of view of teachers and developed solutions for them by the researcher. It also concluded that there are no statistically significant differences between the average scores of teachers' answers to the questionnaire attributed to the variables of academic qualification and years of experience, and that there are differences between the average scores of their answers to the questionnaire attributed to the variable of training courses in the field of educational technology in favor of teachers who underwent a more than one training course in the field of educational technology; Therefore, the study proposed developing a comprehensive strategy in cooperation between the Ministry of Technology and Communications, the Ministry of Education, and the Ministry of Higher Education with the aim of providing the administrative, material, and human requirements necessary for using artificial intelligence in the Syrian educational platform, implementing training courses for teachers on the use of artificial intelligence applications in education, providing material and moral incentives for teachers participating in implementing lessons via the Syrian educational platform, providing modern technologies necessary to develop the performance of teachers participating in implementing lessons via the Syrian educational platform, especially computers and fast Internet lines, and conducting more research and studies that address artificial intelligence in educational and non-educational fields.
Keywords: Artificial Intelligence, Electronic Environments, Syrian educational platform.